The PEMBANGUNAN GAME 3D REAL TIME STRATEGY “BUG INVASION” BERBASIS DESKTOP: Unity 3D Game Engine - Rudi Kurniawan; Rizal Yudha Pradatama (LPPM STMIK AMIK BANDUNG, 2021)
Abstract. The number of new titles offered by games with the Real Time Strategy genre, from the results of observations, in fact not many offer new mechanisms in the game. This study aims to produce a new mechanism by offering a micro-economic method. With the micro-economic method, the game can provide new challenges for players in the form of restrictions (boundaries) in the placement of an object's position, for example, the large number of buildings built in one area cannot be done arbitrarily. In this game also developed an Artificial Intelligence (AI) which is used as an opposing stronghold in a battle simulation against real players (humans). In the 3D game development process, the Multimedia Development Life Cycle (MDLC) method is used, namely (1) Concept stage; (2) Design stage; (3) The stage of collecting materials (images, character models, animation, video, audio and others); (4) Manufacturing stage (combining all objects based on the concept stage and design stage); (5) testing phase, alpha and beta; (6) Distribution stage (game release to target users). The tools used are Game Engine Unity with C# programming language. From the results of testing with this mechanism, a new game that uses a micro-economic method has been able to provide limits on the placement of positions and the number of buildings placed by creating a circle-shaped border centered on each player's town hall and the AI. The creation of a circle-shaped border is used as a marker of the boundary between the Player and the AI. Thus, players and AI will not be able to build the buildings they have and take resources that are outside the boundaries of their borders. Keywords: Real Time Strategy, Micro Economic Method, Unity 3D Navigation System, Simulation Game.